Geometric modeling from the medical images in the CAD system to support prosthesis design - Canciglieri Jr., Osiris; Rudek, M.; Francesconi, Tiago; De Souza, Teófilo Miguel [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2010)
This paper presents an individual designing prosthesis for surgical use and proposes a methodology for such design through mathematical extrapolation of data from digital images obtained via tomography of individual patient's bones. Individually tailored prosthesis designed to fit particular patient requirements as accurately as possible should result in more successful reconstruction, enable better planning before surgery and consequently fewer complications during surgery. Fast and accurate design and manufacture of personalized prosthesis for surgical use in bone replacement or reconstruction is potentially feasible through the application and integration of several different existing technologies, which are each at different stages of maturity. Initial case study experiments have been undertaken to validate the research concepts by making dimensional comparisons between a bone and a virtual model produced using the proposed methodology and a future research directions are discussed.
Keywords: CAD; DICOM; Geometric modeling; Human prostheses; Image processing; Product development; Accurate design; Bone replacement; CAD system; Digital image; Future research directions; Medical images; Prosthesis design; Virtual models; Bone; Design; Geometry; Imaging systems; Industrial engineering; Manufacture; Medical imaging; Research; Soft computing; Surgery; Tomography; Prosthetics